Characteristics Of Kalimantan Community Empowerment To Prevent The Transmission Of Covid-19 In The City Of South Ternate - A Hi Djafar, Monisa (International Journal of Science, Technology & Management, 2022)
Corona virus is a zoonosis (transmitted between animals and humans). Based on scientific evidence, COVID-19 can be transmitted from human to human through coughing/sneezing droplets (droplets). 19 including those treating COVID-19 patients. The purpose of the results of the study was to find out the people of Kalumata to prevent the transmission of covid. The type of research used in this study is quantitative with a Cross Sectional Study design which is one of the observational studies to determine the characteristics of the Kalumata community empowerment to prevent the transmission of COVID-19. Where the research is a Cross Sectional Study, researchers look for characteristics between the independent variable (covid 19 empowerment) and the dependent variable (prevention of transmission) by taking instantaneous measurements. Characteristics of the empowerment of the Kalumata community in preventing the transmission of COVID-19 in the city of South Ternate. The population in this study was the entire number of people who received treatment for COVID-19 patients who carried out examinations at the Kalumata Health Center, South Ternate City, as many as 95 positive COVID-19 patients. The results of the analysis showed that the level of knowledge (62.2%). Compared to the attitude variable (81.8%), compared to the social media variable (94.7%) people know about it compared to Covid sufferers (84.2%). Compared with not suffering that is (15,8%). The conclusion is that it can be suggested because the covid 19 disease is a health problem that occurs without our knowledge, therefore to prevent the transmission of covid 19 to us, it is necessary to have early prevention by preventing various causative factors that trigger triggers that can be controlled, such as public knowledge there is still not enough information about covid 19 so that it can spread to other people.